Translation of Gastronomic Vocabulary in Māris Putniņš’s Novel “Wild Pirogis: A South Sea Tale” - Laurušaitė, Laura (Vertimo studijos, 2025)
As a case study, the article examines the Lithuanian translation of the Latvian children’s novel Mežonīgie pīrāgi: Dienvidjūras pasaka (“Wild Pirogis: A South Sea Tale”) by Māris Putniņš, a text rich in gastronomic metaphors and anthropomorphic food characters. Translating these culturally embedded elements requires balancing linguistic fidelity with creative adaptation to preserve the text’s humour, cultural context, and accessibility for young readers. The analysis highlights the challenges of rendering culturally specific elements—such as food names, character identities, and intertextual references—within a closely related yet distinct language pair. Translating food involves not only linguistic adaptation but also cultural interpretation, navigating between foreignization and domestication strategies. Drawing on gastropoetics and imagology, the study demonstrates how the translation of food shapes national and cultural representations (van Doorslaer 2019). The findings emphasize that food functions not only as a narrative device but also as a means of intercultural exchange, showing how literary translation negotiates between linguistic accuracy and cultural resonance.